Assessing the Efficacy of Pipelle Sampling as Outpatient Diagnostic Test in a Tertiary Care Hospital-Rawalpindi, 2020 - Nusrat Noor , Rabiah Anwar , Rabia Akbar , Ghazala Sadaf , Khan M Yaqub, Nusrat Noor , Rabiah Anwar , Rabia Akbar , Ghazala Sadaf , Khan M Yaqub (Journal of Rawalpindi Medical College, 2020)
Objective: To assess the effectiveness and enlist clinical factors, which may affect effectiveness of Pipelle sampling in diagnosing endometrial pathology in patients with abnormal uterine bleeding and Post-menopausal Bleeding. Study Design: ‘Analytical Cross-Sectional’ study. Place and duration: Gynecology Department at Combined Military Hospital Rawalpindi, in collaboration with Histo-Pathology Department, of six months duration i.e. from 1st December 2019 to 31st May 2020. Patients and methods: 100 female patients of outpatient department with presenting complaints of either abnormal or post-menopausal bleeding were included in the study in the specified time frame. After informed written consent, Pipelle endometrial sampling was done on outpatient basis, and by consecutive sampling technique using lottery method, sample was sent for histopathological evaluation. Evaluated factors studied were: indications for the procedure, age, parity, age of menarche. Results: Of the total patients evaluated, 91% (n=100) were non-malignant, while 4% (n=100) were malignant. Inadequate tissue was obtained in 5% samples. Most common histopathological findings among reproductive age group were Proliferative and Secretory phase endometrium 64% (n=100). While in Post-menopausal age group 4% (n=100) were Endometrial carcinoma on histopathology. Inadequate tissue samples 5% (n=100) were noted among the Post-menopausal group. 6% samples showed endometrial hyperplasia. Pipelle Endometrial Sampling had sensitivity and specificity, in diagnosing the endometrial pathologies is summarized in Table 3. Conclusion: Pipelle Endometrial Sampling is an effective, safe, simple and acceptable procedure for diagnosing endometrial pathology. It is cost effective requiring no anesthesia with high sensitivity and specificity for detecting endometrial pathology.